Conformational analysis of 9β,19-cyclopropyl sterols: Detection of the pseudoplanar conformer by nuclear Overhauser effects and its functional implications - Nes, W. David (1988)
Nuclear Overhauser difference spectroscopy and variable temperature studies of the 9β,19-cyclopropyl sterols 24,25-dehydropollinastanol (4,4-desmethyl-5α-cycloart-24-en-3β-ol) and cyclolaudenol [(24S)-24-methyl-5α-cycloart-25(27)-en-3β-ol] have shown the solution conformation of the B/C rings to be twist-chair/twist-boat rather than boat/chair as suggested in the literature. This is very similar to the known crystal structure conformation of 9β,19-cyclopropyl sterols. The effect of these conformations on the molecular shape is highly significant: the first conformation orients into a pseudoplanar or flat shape analogous to lanosterol, whereas the latter conformation exhibits a bent shape. The results are interpreted to imply that, for conformational reasons, cyclopropyl sterols can be expected to maintain the pseudoplanar shape in membrane bilayers.